PENGARUH SENAM KAKI TERHADAP KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS TYPE II DI RUMAH SAKIT ISLAM BONTANG - Suci Nur Aniah; Hilda; Arsyawina (Jurnal Cakrawala Ilmiah, 2024)
Introduction: Diabetes mellitus is a metabolic disease that continues to increase. Its prevalence in Indonesia ranks third in Southeast Asia at 11.3%. East Kalimantan ranks second after DKI Jakarta at 3.1 million people. Foot exercise can increase blood flow, use of glucose by muscles, burn body calories make capillary nets open and insulin receptors more active which has the effect of lowering blood glucose. This study aims to determine the effect of foot exercises on blood sugar levels in patients with type II diabetes mellitus at the Bontang Islamic Hospital. Method: Type of research Pre-Experimental Design without a control group by intervening diabetic foot exercises where before and after the intervention was checked blood levels of HbA1c and GDP. Samples were taken by purposive sampling totalling 20 people. The research variables on independent blood sugar levels (HbA1c and GDP) and dependent are diabetic foot exercises. Data were analysed univariately and bivariately with the Wilcoxon Signed Ranks Test. Results: The value of HbA1c was obtained, the Z value of HbA1c levels was -3.922, the Z value of GDP levels was -3.91 at the 5% level of segnification The results of the analysis with the test obtained p value = 0.01 <0.05 so that it can be concluded that the research shows a significant difference before and after diabetic foot exercises (p value < α), namely at HbA1c and GDP each 0.01. Conclusion: The decrease in HbA1c and GDP blood levels shows the difference that diabetic foot exercises will help control blood sugar levels if carried out regularly and regularly.